How do you solve the system using the elimination method for 2a + 3b = 6 and 5a + 2b – 4 = 0?

1 Answer
Jul 22, 2015

Answer:

#(a,b) = (0,2)#
#color(white)("XXXX")##color(white)("XXXX")#(using elimination method)

Explanation:

[1]#color(white)("XXXX")##2a+3b = 6#
[2]#color(white)("XXXX")##5a+2b-4=0#

Rewite [2] into standard form:
[3]#color(white)("XXXX")##5a+2b=4#

Multiply [1] by 2 and [3] by 3 to make the coefficients of #b# the same in both.
[4]#color(white)("XXXX")##4a+6b=12#
[5]#color(white)("XXXX")##15a+6b=12#

Subtract [4] from [5]
[6]#color(white)("XXXX")##11a = 0#
Divide by 11
[7]#color(white)("XXXX")##a=0#

Substitute #0# for #a# in [1]
[8]#color(white)("XXXX")##2(0) + 3b = 6#
Simplify
[9]#color(white)("XXXX")##b=2#